Capital structure and profitability of municipal companies in Olsztyn - Skorwider-Namiotko, Jarosław (Olsztyn Economic Journal, 2023)
Municipal companies try to combine the implementation of social goals and municipal tasks in the public utility field with the owner’s commercial goals related to increasing value or maximising financial results. They also use debt capital obtained from the financial market in their activities. The research aims to assess the capital structure in Olsztyn’s municipal companies between 2017 and 2022 and the impact of the adopted capital structure on the profitability of these entities. The subjects of the research were seven municipal-owned companies operating in Olsztyn. The study used economic analysis methods, i.e. comparative analysis, ratio analysis and the Du Pont model according to Hawawini’s proposal. The research shows that these companies generate losses and are primarily profitable in general activities, but their profitability is low. They use debt in their capital structure, often to a significant extent, but employ secure financing strategies. The observed changes in profitability were most often due to changes in operating margins from sales rather than changes in capital structure.